The old and new biochemistry of polyamines - Bae, Dong-Hun; Lane, Darius J.R.; Jansson, Patric J.; Richardson, Des R. (Biochimica et biophysica acta. General subjects, 2018)
Polyamines are ubiquitous positively charged amines found in all organisms. These molecules play a crucial role in many biological functions including cell growth, gene regulation and differentiation. The three major polyamines produced in all mammalian cells are putrescine, spermidine and spermine. The intracellular levels of these polyamines depend on the interplay of the biosynthetic and catabolic enzymes of the polyamine and methionine salvage pathway, as well as the involvement of polyamine transporters. Polyamine levels are observed to be high in cancer cells, which contributes to malignant transformation, cell proliferation and poor patient prognosis. Considering the critical roles of polyamines in cancer cell proliferation, numerous anti-polyaminergic compounds have been developed as anti-tumor agents, which seek to suppress polyamine levels by specifically inhibiting polyamine biosynthesis, activating polyamine catabolism, or blocking polyamine transporters. However, in terms of the development of effective anti-cancer therapeutics targeting the polyamine system, these efforts have unfortunately resulted in little success. Recently, several studies using the iron chelators, O-trensox and ICL670A (Deferasirox), have demonstrated a decline in both iron and polyamine levels. Since iron levels are also high in cancer cells, and like polyamines, are required for proliferation, these latter findings suggest a biochemically integrated link between iron and polyamine metabolism. •Polyamines are ubiquitous positively charged amines found in all organisms.•Polyamines play a crucial role in many biological functions.•Polyamine levels are high in cancer cells and are a therapeutic target.•Several iron chelators have been shown to reduce polyamine levels.•There is a biochemically integrated link between iron and polyamine metabolism.